Struktur Komunitas Mangrove di Pesisir Pantai Cemara Kabupaten Lombok Barat dalam Upaya Penyusunan Modul Ekologi - Utami, Fidiati; Utami, Septiana Dwi; Safnowandi, Safnowandi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
The mangrove habitat found on the coast of Cemara Beach, West Lombok Regency is a river that meets a forest area that merges with the sea. The objectives of this research include: 1) identifying the types of plants that make up the mangrove forest on the Cemara Coast; 2) analyze the abundance of mangroves on the Cemara Coast; 3) analyze the diversity and evenness index of mangroves on the Cemara Coast; 4) reveal the population of species that dominate the mangrove community on the Cemara Coast; 5) analyze differences in mangrove abundance on sandy and muddy substrates on the Cemara Coast; 6) analyze differences in mangrove species diversity on sandy and muddy substrates on the Cemara Coast; 7) analyze the differences in mangrove dominance on sandy and muddy substrates on the Cemara Coast; and 8) develop research results on mangrove community structure as material in preparing ecological modules. This type of research is comparative descriptive. The design in this research uses a plot method with a total of 20 plots, namely 10 plots on a sandy substrate and 10 plots on a muddy substrate with 1 plot measuring 10 x 10 m. Development research using the 4D model from Thiagarajan et al. (1974) which was modified into 3P (Definition, Design and Development). The results of the research showed that there were 5 species of mangroves found on sandy substrates, while there were 4 species on muddy substrates. The abundance of mangrove plants on sandy substrates is 292 species of Sonneratia alba, while on muddy substrates there are 219 species of Rhizophora mucronata. The diversity index for sandy substrates and muddy substrates is 0, so the diversity index is categorized as low species diversity because H'<1. The evenness of mangrove plants is the uneven distribution of organisms in the community. The species that dominates on sandy substrates is Sonneratia alba, while on muddy substrates it is Rhizophora mucronata. The important value index for the level of poles and trees as well as the level of seedlings and saplings on sandy substrates is included in the medium category, because the important value index value ranges between 101% - 200% which is categorized as medium. Based on the results of the analysis of teaching materials, analysis of expert validation results and student readability tests (small group tests), the average achievement level reached 81.15% with very good qualifications. Thus, the plant ecology module teaching materials are suitable for use without revision.